PELATIHAN BUDIDAYA CACING Lumbricus Rubellus SEBAGAI ALTERNATIF PAKAN LELE BERPROTEIN TINGGI PADA PEMBUDIDAYA LELE DI KEC. ABIANSEMAL, KAB. BADUNG - Ernawati, N.M.; Julyantoro, P.G.S.; Suryaningtyas, E.W.; Sari, A.H.W.; Kartika, G.R.A.; Saraswati, S.A.; Pebriani, D.A.A. (Buletin Udayana Mengabdi, 2017)
as one of freshwater commodity which has high economic value. The high market demand of catfish indicated that this species has a good prospect for intensive culture. The intensive culture of catfish fed by artificial feed is one of critical factor for supporting the growth of this species. However, the high price of artificial fish feed is often being an obstacle for the development of catfish intensive culture. In order to find solution of this problem, it’s needed to find low price feed but still has good nutritional content for cultured catfish. One of this solution is by using the live feed which has high protein content namely the worm Lumbricus rubellus. The use of L. rubellus worm as alternative feed can be applied to reduce of the feed cost for catfish intensive culture. Since not all of the fish farmer have good information about using L. rubellus as fish feed, it need a kind of small training to introduce the use of L. rubellus worm as an alternative feed for intensive catfish culture. The purpose of this community service activity is to give information for catfish farmer about the culture technology and use of L. rubellus as alternative feed, theoretically and practically.